2011
DOI: 10.1007/978-1-4419-8414-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin Proteases in Toxoplasma gondii

Abstract: Cysteine proteases are important for the growth and survival of apicomplexan parasites that infect humans. The apicomplexan Toxoplasma gondii expresses five members of the C1 family of cysteine proteases, including one cathepsin L-like (TgCPL), one cathepsin B-like (TgCPB), and three cathepsin C-like (TgCPC1, 2 and 3) proteases. Recent genetic, biochemical and structural studies reveal that cathepsins function in microneme and rhoptry protein maturation, host cell invasion, replication, and nutrient acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
(103 reference statements)
0
39
0
Order By: Relevance
“…It is classified into seven categories based on the key catalase residues in an active location: Aspartic, cysteine, glutamic, serine, threonine, metallic, and chromium, which can be divided into more families [16]. This enzyme is important for the growth and survival of parasites in humans [17]. Lagal et al reported that host cell invasion by T. gondii is critically dependent on adhesive proteins secreted from the micronemes.…”
Section: Resultsmentioning
confidence: 99%
“…It is classified into seven categories based on the key catalase residues in an active location: Aspartic, cysteine, glutamic, serine, threonine, metallic, and chromium, which can be divided into more families [16]. This enzyme is important for the growth and survival of parasites in humans [17]. Lagal et al reported that host cell invasion by T. gondii is critically dependent on adhesive proteins secreted from the micronemes.…”
Section: Resultsmentioning
confidence: 99%
“…Cathepsin proteases act clasically as lysosomal hydrolases that digest endogenous and exogenous endocytosed polypeptides [706] . They function in microneme and rhoptry protein maturation, host cell invasion, replication, and nutrient acquisition [707,708] . Que et al [705] showed that the TgCatB, toxopain-1, was localized to rhoptries (secretory organelles required for parasite invasion into cells), and was critical for parasite invasion and rhoptry protein processing.…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…It was demonstrated that T. gondii tachyzoites ingested host cytosolic proteins and digested them using CatL and other proteases within its endolysosomal system [708] . Both virulent type I and avirulent type II strain parasites ingested and digested hostderived proteins, indicating that the pathway is not restricted only to highly virulent strains.…”
Section: T Gondii Infectionmentioning
confidence: 99%
See 2 more Smart Citations